Immobilization of solidified ceramic forms with magnesium phosphate cement. Issue 10 (July 2019) - Zhenyu, Lai; Yang, Hu; Tao, Yan; Xin, He; Zhongyuan, Lu; Shuzhen, Lv; Haibin, Zhang
Abstract: Ceramic solidification offers higher waste loading and a more stable state than can be provided by the glass solidification method because of the stable crystalline structure of its forms, but the process of fabricating large bulk solidified ceramic forms is complicated and therefore limited in application. In this paper, particulate ceramic solidification forms were first prepared by using high-temperature sintering; particulate ceramic solidification forms were then added into a paste of magnesium phosphate cement (MPC), which form composite solidified forms after curing. The mechanical and durability properties of the samples were investigated, and the phases, microstructure, high-temperature stability, and leaching properties of samples were measured by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, and inductively coupled plasma mass spectrometry. The results show that the solidified forms prepared have excellent mechanical properties, high-temperature stability, soaking resistance, and freeze–thaw resistance. The compressive strength of samples decreased with increasing ceramic content, with the strength reaching 27.8 MPa with a 50 wt% load content of ceramic. With adsorption of the simulated nuclides by the hydration products of cement and the retardation effect of MPC, the leaching rate of the simulated nucleus was found to be 1.86 × 10 −7 cm/day, which is less than that of the ceramic solidified form. A protective layer on the surface of the solidified ceramic form with MPC can further improve the performance of the solidified form.